2010
DOI: 10.1186/1472-6920-10-77
|View full text |Cite
|
Sign up to set email alerts
|

Use of simulator-based medical procedural curriculum: the learner's perspectives

Abstract: BackgroundSimulation is increasingly used for teaching medical procedures. The goal of this study was to assess learner preferences for how simulators should be used in a procedural curriculum.MethodsA 26-item survey was constructed to assess the optimal use of simulators for the teaching of medical procedures in an internal medicine residency curriculum. Survey domains were generated independently by two investigators and validated by an expert panel (n = 7). Final survey items were revised based on pilot sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 21 publications
(29 reference statements)
4
44
0
3
Order By: Relevance
“…It is uncertain whether the abilities demonstrated in this simulated setting will translate to improved performance in the real clinical environment. Simulation-based education is generally considered effective, 6 and most studies conclude that it is beneficial before transitioning to clinical procedures. 15 Results of studies in laparoscopy, colonoscopy and central line insertion have shown that participants achieve better clinical performance in these skills when they are trained on a simulator beforehand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncertain whether the abilities demonstrated in this simulated setting will translate to improved performance in the real clinical environment. Simulation-based education is generally considered effective, 6 and most studies conclude that it is beneficial before transitioning to clinical procedures. 15 Results of studies in laparoscopy, colonoscopy and central line insertion have shown that participants achieve better clinical performance in these skills when they are trained on a simulator beforehand.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated environment is increasingly being used for learning procedural skills, including LP, 6 because it permits repetitive practice while avoiding undue risk to patients. It provides a safe environment to learn and practice technical skills with the advantages of reducing both time pressures and fear of harming the patient.…”
Section: Résumémentioning
confidence: 99%
“…La simulación se puede utilizar para introducir nuevos conceptos y evaluar competencias especificas (3) . Por otra parte, el marco teórico y conceptual de la simulación médica está centrado en el concepto de competencias.…”
Section: Introductionunclassified
“…10 Gaining a better understanding of learners' perspectives can assist educators in the implementation of a specific simulation curriculum. 3 Seattle Children's Hospital opened a new emergency department (ED) in April 2013 that includes a JIT training room, conveniently located within the ED clinical space, and is available 24 hours a day for procedural education in splinting, suturing, and lumbar puncture (LP). This room is used daily for physician and nurse education, but is always available for JIT training.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies [1][2][3][4][5][6][7][8][9] have examined JIT training, yet there are no known studies examining the use of dedicated JIT space to practice common procedures near the clinical space, rather than a simulation center. Simulation-based education, as in the JIT room, can provide a reproducible standard environment for deliberate practice as well as both formative and summative assessment.…”
Section: Introductionmentioning
confidence: 99%